STRATEGI PEMASARAN BUDIDAYA IKAN LELE PADA UD KARYA TANI DI KOTA LHOKSUEMAWE - Nanda Ameliany; Nursakinah Ritonga; Hafizatun Nisak (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
Marketing strategy is used to support activities in increasing the income of a business. The contribution of this research is to find out the marketing strategy used in catfish farming and what obstacles are found in the marketing strategy of catfish farming in Karya Tani Tumpok Teungoh, Banda Sakti District, Lhokseumawe City. Study Approach Based on qualitative research methods. The informants in this study were the owners, employees and customers of catfish at UD Karya Tani. Data analysis techniques include data reduction, data presentation and drawing conclusions. The researcher concludes that the marketing strategy for the catfish business at UD. Karya Tani is less effective and efficient because the identification of UD Karya Tani's customers does not increase, the business location is less strategic for marketing, promotional and marketing media are minimal, customer relations are limited. Constraints that occur include technical constraints, passive and minimal promotion constraints as well as poor distribution channels and ongoing handling efforts to optimize the applied marketing strategy.